Introduction: Social Innovation and Social Policy. Issue 3 (3rd June 2014) - Baglioni, Simone; Sinclair, Stephen
<x content-type="archive" xml:space="preserve">Abstract</x> This themed section discusses the conceptual development and related empirical applications of social innovation (SI), a concept acquiring a prominent position in both academia and the world of policy. When SI started being used in the early 1990s relatively few social scientists were familiar with it, mainly those interested in urban policy. Less than two decades later, not only is SI at the heart of the largest public research funding programme in Europe (Horizon 2020), it is also constantly referred to in the discourses of senior level policy makers on both sides of the Atlantic.